Dosis de cuyaza en las características agronómicas y rendimiento de Brassica Juncea L. mostaza de hoja, Loreto.2024 - Carbajal Reategui, Roni Darwin (2025)
The objective of this research was to evaluate the effect of different doses of cuyaza on the agronomic characteristics and yield of Brassica juncea L. Mustard greens in the Loreto region of Peru. A randomized complete block design (RCBD) was used with four treatments (10, 20, 30, and 40 t/ha of cuyaza) and four replicates. Agronomic variables measured included plant height, plant width, leaf weight, number of leaves, stem length, and root length. The results indicated that the 40 t/ha dose of cuyaza had the greatest effect on plant height, plant width, and leaf weight. In contrast, no significant differences were observed in the number of leaves per plant. Furthermore, the total plant weight increased significantly with the highest dose of cuyaza. It is concluded that cuyaza is a highly effective biofertilizer for improving the growth and yield of mustard greens. The 40 t/ha dose showed the greatest effect on the agronomic variables evaluated. In particular, leaf weight averaged 35.6 g (p < 0.01), while plant weight showed a significant increase with an average value of 120 g (p < 0.001) compared to lower doses. These results suggest that applying cuyaza at a dose of 40 t/ha not only optimizes vegetative development but also maximizes plant yield.